Viaje póstumo a París del Faraón Ramsés II - Llagostera, Esteban (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2010)
Por primera vez en la historia, un faraón egipcio viaja al extranjero. Su momia, fue trasladada a París, para «curarla» de las múltiples invasiones de bacterias, insectos necrófagos, microbios y hongos de los que estaba invadido, además de múltiples fracturas. E igualmente, para diagnosticar las causas de su muerte. El traslado de El Cairo a París y regreso, se realizó con un avión militar francés. Egipto, notificó a Israel este vuelo extraordinario, para evitar cualquier problema que pudiera surgir, en aquella zona tan conflictiva de Oriente Medio. En cuanto el avión penetro en el espacio aéreo francés, dos reactores militares le dieron escolta hasta el aeropuerto de Le Bourget-París, donde se le rindieron honores de Jefe de Estado. Toda Francia se puso a disposición de Ramsés el Grande. Mme. Desroches- Noblecourt, Inspectora General a Perpetuidad de los Museos Estatales de Francia, no lo abandonó ni un momento y voló con él desde Heliopolis hasta París y su posterior regreso a El Cairo. When French scientists informed Mme. Desroches-Noblecourt, Inspector General of National Museums, of the poor state of preservation of the mummy of pharaoh Ramesses II (he suffered from bacteria, necrophagus insects, fungus, etc.), she immediately informed the President of France, who made a quick trip to inform the Egyptian President about the news. Giscard d’Estaing suggested taking the mummy to Paris in a special plane. Due to the political situation of the time and because Ramesses II would be travelling in a military plane, Egypt informed Israel about the special conditions surrounding this extraordinary flight. This was to be the first time in History that an Egyptian pharaoh «travelled» to a foreign country. The plane departed from Cairo’s Heliopolis Airport where the royal passenger was treated to the honours of a living king. The date was September 26th, 1976. The moment the plane entered French air space; two air force fighters escorted the late pharaoh to Paris. Upon his arrival at the military airport of Le Bourget- Paris, the mummy was received with all the honours of a ruling president. After the formal reception and following the personal wish of the French President, the mortuary car went to the «Place de la Concorde» so that Ramesses II could again «see» his obelisk of Luxor temple. At the Musée de l’Homme everything was ready in two large rooms: one was the laboratory and the other was where the pharaoh would rest at night, always protected by policemen. For the next eight months, the scientists examined the mummy to determine the exact causes of the damage. Ramesses II was very ‘ill’, and everything was to be done to spare him a second death. There was no limit in means or efforts. All France was at Ramesses the Great’s disposal. For the first time ever, they performed a biostereometry on a human body that made it possible to accurately reconstruct the pharaoh’s original features. Whwn he was «healed» of his multiple ailments, he was carefully packed in a very special (fireproof, waterproof, shockproof and floatable) coffin. On May 10th, 1977, and with the same ceremonial protocol, the royal mummy returned to his country of origin. Mme. Desroches-Noblecourt was with him permanently; since his departure from Cairo until his return back to Egypt.